Globalisasi dan Desentralisasi dalam Permasalahan Pembangunan di Papua Barat Daya - Pamungkas, Agfajrina Cindra; Yoga Andriyan; Muhamad Hasan Rumlus; Siti Maysharo Kalauw (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
The expansion of provincial boundaries in 2022 gave rise to a new and youngest province, namely West Papua, with its capital in Sorong. Law No. 20 of 2001 granted Papua broader authority in the implementation of Special Autonomy. It explicitly states that the people of Papua and West Papua are entitled to equitable development. However, alongside the development of globalization, widespread economic development aimed at improving welfare does not necessarily align with policies that should enhance the standard of living for the people of Papua. Instead, it has led to the exploitation of natural resources and failed to improve the quality of life for the Indigenous Papuan People (OAP) because industrial development is driven by large corporations. This paper aims to analyze the interconnection between globalization and decentralization in line with the implementation of Special Autonomy in West Papua. The perspective of globalization refers to economic liberalization in decentralization to analyze development issues in West Papua by examining foreign and domestic investment as threats to the welfare of the indigenous Papuan community. The implementation of decentralization through Special Autonomy over the past twenty-three years, particularly for the Indigenous Papuan people, has not had a significant impact on sustainable development, especially regarding natural resources. The central government's policy through the Job Creation Law aims to expand foreign investment without considering the land rights and customary rights of the Indigenous Papuan people in West Papua.